White Matter Abnormalities and Working Memory Impairment in Systemic Lupus Erythematosus - Kozora, Elizabeth (2013)
OBJECTIVE/BACKGROUND: Many patients with systemic lupus erythematosus (SLE) have working memory deficits. Few studies have evaluated working memory performance and neurometabolite profile using magnetic resonance spectroscopy (MRS) in SLE. METHODS: We gave the Paced Auditory Serial Addition Test (PASAT), a measure of working memory, to 73 patients with SLE. We calculated total score, dyads, chunking, and cognitive fatigue. Using MRS, we determined the ratio of choline to creatine (Ch/Cr) in normal-looking right and left frontal lobe white matter. RESULTS: Twenty-nine percent of patients showed impaired working memory on the PASAT. Total PASAT score inversely correlated with right and left frontal white matter Ch/Cr. Left frontal white matter Ch/Cr correlated with percent chunking and inversely correlated with total and percent of dyads. Right frontal white matter Ch/Cr correlated with percent chunking and inversely correlated with total and percent dyads. There was no relationship between cognitive fatigue and either left or right frontal white matter Ch/Cr. Longer disease duration was associated with higher left frontal white matter Ch/Cr. Correlations remained significant between left frontal white matter Ch/Cr and total PASAT score and total dyads when disease duration was considered. CONCLUSIONS: Patients with SLE were impaired on the PASAT. Lower total PASAT score and fewer dyads correlated with higher left frontal microstructural white matter damage, while cognitive fatigue did not. This pattern suggests that early white matter damage interferes with working memory in SLE and provides further insight into the neurobiological basis of mild cognitive dysfunction related to microstructural white matter injury.